Volume 9: Transportation Systems; Safety Engineering, Risk Analysis and Reliability Methods; Applied Stochastic Optimization, U 2011
DOI: 10.1115/imece2011-65416
|View full text |Cite
|
Sign up to set email alerts
|

Step Ladder Failure Analysis: A Comparison of Analytical Methods

Abstract: When a user falls from a step ladder, the accident can be accompanied by damage to the ladder. A common area of damage is in the vicinity of the connections between the front side rails and the lowermost step. When determining the cause of a fall, it is important to understand how this damage occurs and whether it may be causal to the accident or a result of the accident. Commonly, engineers investigating such accidents have relied on three methods of structural analysis: classic analytical methods (so-called … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is because the assumptions, simplification and conditions for the simulations to reproduce the incident are difficult to make. Kenner et al [5] examined such factors in the analysis of step ladder damaged in the field and concluded that these structures were more complex than they might appear. In fact, in an investigation on the root cause analysis [6] they showed that the ladder was damaged as the result of the user impact of the ladder after substantially tipping over.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the assumptions, simplification and conditions for the simulations to reproduce the incident are difficult to make. Kenner et al [5] examined such factors in the analysis of step ladder damaged in the field and concluded that these structures were more complex than they might appear. In fact, in an investigation on the root cause analysis [6] they showed that the ladder was damaged as the result of the user impact of the ladder after substantially tipping over.…”
Section: Introductionmentioning
confidence: 99%